Taxonomy of centralization in public blockchain systems: A systematic literature review. Issue 4 (July 2021) - Sai, Ashish Rajendra; Buckley, Jim; Fitzgerald, Brian; Gear, Andrew Le
Abstract: Bitcoin introduced delegation of control over a monetary system from a select few to all who participate in that system. This delegation is known as the decentralization of controlling power and is a powerful security mechanism for the ecosystem. After the introduction of Bitcoin, the field of cryptocurrency has seen widespread attention from industry and academia, so much so that the original novel contribution of Bitcoin, i.e., decentralization, may be overlooked, due to decentralizations' assumed fundamental existence for the functioning of such crypto-assets. However, recent studies have observed a trend of increased centralization in cryptocurrencies such as Bitcoin and Ethereum. As this increased centralization has an impact the security of the blockchain, it is crucial that it is measured, towards adequate control. This research derives an initial taxonomy of centralization present in decentralized blockchains through rigorous synthesis using a systematic literature review. This is followed by iterative refinement through expert interviews. We systematically analyzed 89 research papers published between 2009 and 2019. Our study contributes to the existing body of knowledge by highlighting the multiple definitions and measurements of centralization in the literature. We identify different aspects of centralization and propose an encompassing taxonomy of centralization concerns. This taxonomy is based on empirically observable and measurable characteristics. It consists of 13 aspects of centralization, classified over six architectural layers: Governance, Network, Consensus, Incentive, Operational, and Application. We also discuss how the implications of centralization can vary depending on the aspects studied. We believe that this review and taxonomy provides a comprehensive overview of centralization in decentralized blockchains involving various conceptualizations and measures. Highlights: Centralization in blockchains cannot be adequately described using the binary notion. Our taxonomy captures 13 aspects of centralization over 6 architectural layers. We apply the taxonomy to Bitcoin and Ethereum and present empirical results. Empirical results suggest centralization may not always have a negative implication.